Scientific and Practical Issues of Mapping the Ecoturist Situation on the Example of Fergana Region - Mirzarakhmat kizi, Mirzakarimova Gulshanoy; Yuldosh ugli, Rasulov Asror; Khudoynazarovich, Turdikulov Khusanboy; Rakhimjonovna, Khakimova Kamolaxon; Abduraufovich, Kayumov Odiljon (Research in Ecology, 2025)
Ecotourism is one of the fastest-growing sectors globally, playing a crucial role not only in economic development, job creation, and improving living standards but also in ensuring ecological balance and sustainable development. The Fergana region, with its diverse natural landscapes, historical and cultural heritage, and recreational opportunities, represents one of the most promising areas for the expansion of ecotourism in Uzbekistan. Therefore, this study focuses on identifying the ecotourism resources of the region, classifying them into categories, developing a territorial typology, and visualizing them through cartographic approaches. The research methodology was based on ArcGIS software and modern GIS technologies. Statistical data, existing general and thematic maps, and remote sensing materials were integrated into a unified cartographic database. Using analytical, synthetic, and complex cartographic methods, the ecotourism resources of the Fergana region were classified into high, medium, and low-potential categories. As a result, natural-geographical complexes such as deserts, foothills, mountain steppes, and forest zones, along with historical-cultural monuments and service infrastructure, were systematized and mapped. Furthermore, theoretical and methodological foundations were developed for the creation of the “ECO FERGANA” mobile application, which aims to provide interactive access to ecotourism sites and routes. The findings demonstrate that GIS-based cartographic approaches are highly effective in assessing and visualizing the ecotourism potential of the Fergana region. The results contribute significantly to expanding ecotourism opportunities, improving tourism infrastructure, and enhancing the competitiveness of the region in both national and international tourism markets. The scientific novelty of the study lies in the comprehensive application of modern GIS technologies and cartographic modeling to evaluate, classify, and present ecotourism resources in an innovative way.